2014
DOI: 10.1159/000363578
|View full text |Cite
|
Sign up to set email alerts
|

Pertussis Toxin Administered Spinally Induces a Hypoglycemic Effect on Normal and Diabetic Mice

Abstract: Background/Aims: To show whether intrathecal (i.t.) treatment with pertussis toxin (PTX) produces a hypoglycemic effect in ICR, db/db and streptozotocin-treated mice. Methods: The blood glucose level (BGL) was measured after i.t. treatment with PTX, AB5 toxins and PTX subunits. Insulin or leptin levels were measured after PTX injection. The effect of PTX on the BGL was examined in adrenalectomized (ADX) mice. Glucose transporter (GLUT) levels were determined by Western blotting. Results: PTX attenua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 49 publications
1
11
0
Order By: Relevance
“…These results suggest that inhibitory G-protein located at the spinal cord appear to be involved in the production of hyperglycemia and protective effect by activations of α 2 -adrenergic receptors located in the spinal cord against sepsis+induced mortality. The inhibitory effect of PTX against clonidine-induced hyperglycemia is in line with our previous study [ 38 ]. It is suggested that blocking the effect of PTX against the hyperglycemic effect induced by clonidine appears to be responsible for antagonizing clonidine-induced protective effect against sepsis-induced mortality.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…These results suggest that inhibitory G-protein located at the spinal cord appear to be involved in the production of hyperglycemia and protective effect by activations of α 2 -adrenergic receptors located in the spinal cord against sepsis+induced mortality. The inhibitory effect of PTX against clonidine-induced hyperglycemia is in line with our previous study [ 38 ]. It is suggested that blocking the effect of PTX against the hyperglycemic effect induced by clonidine appears to be responsible for antagonizing clonidine-induced protective effect against sepsis-induced mortality.…”
Section: Discussionsupporting
confidence: 91%
“…After brief sonication to shear DNA and reduce viscosity, the concentration of protein was determined with the detergent-compatible protein assay reagent (Bio-Rad Laboratories, USA) using bovine serum albumin as the standard. The western blot analysis was performed according to our previous study [ 38 42 ]. The membranes were then exposed to a Luminescent Image Analyzer (LAS-4000, Fuji Film Co., Japan) for the detection of light emission.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the present study was designed to find out the role of supraspinally and spinally located PTX sensitive G-proteins in blood glucose regulation under various types of stress conditions. We and others have previously demonstrated that PTX administered systemically or centrally exerts a hypoglycemic effect [254142]. In addition, i.t.…”
Section: Discussionmentioning
confidence: 99%
“…We have also recently reported In our previous studies, we have reported that i.t. administration with PTX causes hypoglycemia in a comprehensive manner and induced neuroprotection against the KA-induced hippocampal CA3 neuronal death by lowering the blood glucose level [2425]. Although PTX is involved in the regulation of the blood glucose level, However, the exact role of PTX-sensitive G-proteins in stress-induced hyperglycemia has not been well characterized yet.…”
Section: Introductionmentioning
confidence: 99%